Complete involution of prenatally-diagnosed fetal scalp hemangioma - Eun Ju Jo; Suk-Joo Choi; Soo-young Oh; Byung Kwan Park; Cheong-Rae Roh; Jong-Hwa Kim (Elsevier, 2014)
Objective: Scalp hemangioma is a rare benign fetal tumor. Here, we describe the detailed imaging features and natural course of a fetal scalp hemangioma until 1 year of age. Case report: We encountered a case of scalp hemangioma at 23 weeks' gestation by prenatal ultrasonography and magnetic resonance imaging. The mass persisted postnatally, but spontaneously regressed after birth. Conclusion: Proper diagnosis with prenatal ultrasonography and magnetic resonance imaging is important when a scalp mass is suspected in utero. Continuation of the pregnancy after appropriate counseling is prudent, considering the favorable prognosis and the rate of spontaneous regression of uncomplicated cases.